Comparative phytochemical evaluation and biological activity screening of Murdannia nudiflora and Tradescantia pallida - Huq, Samin (BRAC University, 2015)
This project report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2015